Efektivitas Lembaga Birokrasi Dan Tingkat Korupsi Terhadap Investasi Pada Enam Negara Asean (Filipina, Indonesia, Malaysia, Myanmar, Singapura, Dan Thailand) Tahun 2004-2010 - Putra Perdana; Purbayu Budi Santosa (Diponegoro Journal of Economics, 2012)
ABSTRACT This study aims to look the relationship between effectiveness of the bureaucracy against investment into the corruption variable acts as a moderating variable in the six ASEAN countries: Philippines, Indonesia, Malaysia, Singapore and Thailand during 2004-2010. By using Pooled Least Square approach, this study process six variables in the governance indicators, proposed by Daniel Kaufmann, et. al. Pooled least square method with partial regression performed to reduce accuracy of the identified models with multicollinearity among these with corruption variable and investment variable. The results of this study show a relationship of the degree of openness, the level of political stability, the level of legislation, and the level of corruption control in six ASEAN countries against corruption and show a relationship from corruption with investment.